Factors Associated with Diarrhoea Prevalence in Saudi Arabia - Al-Mazrou, Yagob Y. (Medknow Publications & Media Pvt Ltd, 1995)
The weather of Saudi Arabia is hot and dry for most of the year. The country is devoid of surface water which often help the transmission of diarrhoeal diseases. Nevertheless, this country is not free from diarrhoeal diseases. The role of such factors as crowding, patterns of water use, sanitation, quality of housing, feeding practices and region of residence have not been adequately studied. The 1987 National Child Health Survey data were used to earmark the roles of the aforementioned determinants of diarrhoea in Saudi children aged below six. A stratified and representative sample of 8,566 married women living in rural and urban areas were interviewed by 120 female nurses. There were about two episodes of diarrhoea per child per year. Children aged 6 to 23 months had nearly double the prevalence rate of the older children. Children from rural areas and the southern region had higher rates than children from other areas. Children who were both breast and bottle fed, children of 1-4 member families and of families with 3 or more persons per room had higher prevalence rates. Children of families whose homes had earthen floors, those who used well water and those without toilet facilities who used open fields for defecation had significantly higher rates. In spite of adverse climate and little use of surface water these factors were significantly associated with higher prevalence rates of diarrhoea in Saudi children under six years of age.